Bypassing the guardian: regulated cell death pathways in p53-mutant cancers - Jonathan Y. Chung; Bruce A. Knutson (Cellular & Molecular Biology Letters)
Abstract Approximately half of all cancers bear mutations in the tumor suppressor p53. Despite decades of research studying p53 function, treatment of p53-mutant cancers remains challenging owing to the effects of p53 mutations on many complex and interrelated signaling networks that promote tumor metastasis and chemoresistance. Mutations in p53 promote tumor survival by dysregulating cellular homeostasis and preventing activation of regulated cell death (RCD) pathways, which normally promote organismal health by eliminating dysregulated cells. Activation of RCD is a hallmark of effective cancer therapies, and p53-mutant cancers may be particularly susceptible to activation of certain RCD pathways. In this review, we discuss four RCD pathways that are the targets of emerging cancer therapeutics to treat p53-mutant cancers. These RCD pathways include E2F1-dependent apoptosis, necroptosis, mitochondrial permeability transition-driven necrosis, and ferroptosis. We discuss mechanisms of RCD activation, effects of p53 mutation on RCD activation, and current pharmaceutical strategies for RCD activation in p53-mutant cancers. Graphical Abstract